2008
DOI: 10.1080/13625180802075315
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the subdermal contraceptive etonogestrel implant (Implanon®) on biochemical and hormonal parameters (three years follow-up)

Abstract: Our findings confirm data from the literature according to which Implanon does not affect meaningfully reproductive hormonal parameters, thyroid function, hepatic and renal functions, and glucose metabolism. However, further studies are needed to elucidate lipid metabolism changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 15 publications
1
7
0
2
Order By: Relevance
“…In contrast with the injectable depot medroxyprogesterone acetate, which suppresses ovarian estradiol production, estradiol levels remain physiologic in ENG implant users. 62,63 Accordingly, loss of bone mineral density would not be anticipated in users. Few high-quality studies have assessed ENG implant-associated changes in BMD and none have examined adolescents, whose use of hormonal contraceptives during peak bone mineral density accrual has attracted attention.…”
Section: Bone Densitymentioning
confidence: 99%
“…In contrast with the injectable depot medroxyprogesterone acetate, which suppresses ovarian estradiol production, estradiol levels remain physiologic in ENG implant users. 62,63 Accordingly, loss of bone mineral density would not be anticipated in users. Few high-quality studies have assessed ENG implant-associated changes in BMD and none have examined adolescents, whose use of hormonal contraceptives during peak bone mineral density accrual has attracted attention.…”
Section: Bone Densitymentioning
confidence: 99%
“…These changes cannot be considered as adverse effects because the levels were always within normal ranges. Fortunately, this pattern of non-adverse effects remains similar when the SCI is used for longer periods of time [35]. …”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the above trials, Funk and colleagues16 reported no significant change in liver function parameters over a two-year use of the ENG implant. Additionally, Inal and colleagues11 found no significant difference between baseline and end-of-study serum glutamic oxalate transaminase, serum glutamic pyruvic transaminase, fasting glucose, HDL, cholesterol, or triglycerides. The mixed results suggest that there may be a small amount of liver dysfunction in ENG implant users.…”
Section: Safety and Side Effect Profilementioning
confidence: 94%